Application of sodium silicate retards apple softening by suppressing the activity of enzymes related to cell wall degradation. (31st October 2018) - Ge, Yonghong; Duan, Bin; Li, Canying; Wei, Meilin; Chen, Yanru; Li, Xue; Tang, Qi
Abstract: BACKGROUND: During the storage of apples, apple softening is one of the main problems. Sodium silicate has been used to enhance disease resistance and maintain quality of fruits. In the present study, apple fruit (cv. Golden delicious) were treated with 100 mmol L –1 sodium silicate for 10 min and stored at 20 °C to investigate its effects on weight loss, flesh firmness, and the activity of cell wall‐degrading enzymes. RESULTS: The results indicated that 100 mmol L –1 of sodium silicate treatment delayed the increase of weight loss and decrease of the flesh firmness in apples. Sodium silicate treatment also suppressed the activity of polygalacturonic acid transeliminase and pectin methyltranseliminase, pectin methylgalacturonase, polygalacturonase, cellulase and β‐galactosidase in the fruit. CONCLUSIONS: Delaying apple softening by sodium silicate treatment is closely related to the inhibition of the activity of cell wall‐degrading enzymes and weight loss. © 2018 Society of Chemical Industry